Ecological and Biocenotic Aspects of the Legal Regime of Animals - Teleuyev Г.Б.; Bekturganov А.Е.; Zhussipova Б.А. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
This article explores the ecological and biocenotic aspects of the legal regime of animals, highlighting the importance of effective legal regulation in ensuring biodiversity and maintaining ecological balance. Animals play a crucial role in ecosystems, contributing to the stability and health of biocenoses. However, the increasing human impact on the environment necessitates the development of legislative measures to protect wildlife and regulate human interaction with it. The study addresses key issues such as the classification of animals according to their legal status, the differentiation of measures for their protection, and the implementation of international standards in national legislation. Special attention is given to the legal mechanisms for protecting endangered species and ensuring sustainable management of natural resources. The article also discusses the challenges of harmonizing environmental law with the principles of economic development. Recommendations are provided for improving legislation to strengthen the legal framework for animal protection and promote the integration of ecological considerations into policymaking. The findings emphasize the need for a comprehensive approach to legal regulation that incorporates scientific research and public awareness to achieve effective protection of biodiversity and ecological systems. The scientific article was prepared as part of the implementation of the project AP19679495 «Issues of Regulating the Legal Status of Animals: Domestic and Foreign Experience», funded by the Committee of Science of the Ministry of Science and Higher Education of the Republic of Kazakhstan.